A comparison of data collection methods: Mail versus online surveys. (15th March 2018) - Loomis, David K.; Paterson, Shona
Abstract: Online surveys offer an alternative to mail, telephone, and on-site techniques for gathering data. However, criticisms of Internet surveys, including survey and item nonresponse bias, and differences in the nature of the data have been raised. A total of 11 data sets were collected at Zuma Beach, California; within various state parks and forests in Massachusetts; at Buck Island Reef National Monument, USVI; and at Dry Tortugas National Park, Florida. These studies were designed, in part, to test for differences between the modes of survey delivery. Data for each study site were collected via both mail and Internet surveys, with the mail and Internet surveys being identical for each study location. Results indicate that while some differences exist between mail and online surveys at the individual study level, these differences are not present when the studies are combined and that mode differences observed for individual studies may be idiosyncratic rather than mode specific.